2019
DOI: 10.1007/s11894-019-0690-9
|View full text |Cite
|
Sign up to set email alerts
|

Controversies in the Management of Functional Constipation in Children

Abstract: Purpose of review Functional constipation (FC) in children is a common health problem with reported worldwide prevalence rates up to 32.2%. The majority of children with constipation respond to oral laxative treatment. After 5 years of intensive treatment, however, approximately 50% of children remain symptomatic. To discuss the evidence for new treatments in these children, including pre-and probiotics, pelvic physiotherapy, prucalopride, sacral nerve stimulation, and surgery, and to highlight the controversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 72 publications
0
37
0
Order By: Relevance
“…Toilet-trained children were significantly more likely to meet diagnostic criteria for FC than non-toilet-trained children, 41.9% vs 9.3%, respectively (OR 7.06, 95% CI 5.26-9.47, P < .0001). Children that were toilet-trained were also more likely to report 3…”
Section: Functional Constipation and Toilet Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Toilet-trained children were significantly more likely to meet diagnostic criteria for FC than non-toilet-trained children, 41.9% vs 9.3%, respectively (OR 7.06, 95% CI 5.26-9.47, P < .0001). Children that were toilet-trained were also more likely to report 3…”
Section: Functional Constipation and Toilet Trainingmentioning
confidence: 99%
“…to be efficacious in childhood. 3,4 Studies have shown that delayed treatment worsens the outcome. 5 Most children develop constipation as infant or toddlers.…”
mentioning
confidence: 99%
“…The other three patients who were older children or in early adulthood had no significant abdominal signs, and their gastrointestinal presentation was only difficulty with defecation. With constipation as a gastrointestinal presentation in older children, more than 90% of the cases are functional in nature [5], and it is uncommon to associate constipation with intractable anemia. Thus, a diagnosis of HD can be missed.…”
Section: Discussionmentioning
confidence: 99%
“…Bowel disorders treated with SNS/SNM include sphincter disruption, evacuation difficulty, neurogenic bowel dysfunction, irritable bowel syndrome (IBS), and constipation (13,43). Three systematic reviews (29,31,34), five reviews (33,(43)(44)(45)(46) (Table 4A) and seven studies (47)(48)(49)(50)(51)(52)(53) (Table 4B) conclude the evidence is limited, and that SNS is not effective for constipation. There may be some value in children (50), but more studies are required (36).…”
Section: Sns/snm and Constipationmentioning
confidence: 99%